2021
DOI: 10.3390/f12091186
|View full text |Cite
|
Sign up to set email alerts
|

Productivity of Eucalyptus pellita in Sumatra: Acacia mangium Legacy, Response to Phosphorus, and Site Variables for Guiding Management

Abstract: We report on experimental studies conducted in South Sumatra with interrelated objectives to (i) examine the trends in production covering 30 years, including three rotations of Acacia mangium followed by Eucalyptus pellita which replaced A. mangium for managing the widespread threat of diseases; (ii) understand the effects of inter-rotation slash and litter management applied to acacia (legacy effects) on E. pellita growth; (iii) assess the long term changes in the top soil layer arising from above; (iv) eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
(86 reference statements)
3
12
1
Order By: Relevance
“…It has been well documented that the addition of P at planting time markedly improves the early growth of E. pellita and that the growth response is sustained towards the end of rotation, although the proportional response declines over time [3,4]. In contrast, we found that application of P at age 1 year (in addition to P fertiliser given at establishment) did not result in any further additional growth of E. pellita throughout the rotation.…”
Section: Influence Of Fertilisation In Mid-rotation On Productivitycontrasting
confidence: 46%
See 4 more Smart Citations
“…It has been well documented that the addition of P at planting time markedly improves the early growth of E. pellita and that the growth response is sustained towards the end of rotation, although the proportional response declines over time [3,4]. In contrast, we found that application of P at age 1 year (in addition to P fertiliser given at establishment) did not result in any further additional growth of E. pellita throughout the rotation.…”
Section: Influence Of Fertilisation In Mid-rotation On Productivitycontrasting
confidence: 46%
“…The lack of response and decline in response to P fertiliser applied at 1 year after planting is influenced by high internal nutrient retranslocation rates for P (54.6-73.2%), N (24.9-33.0%), and K (40.2-49.0%), while there was minimal retranslocation of Ca and Mg [17]. External cycling through litter after canopy closure is also important, with litterfall of E. pellita at Sodong being measured at 8.7 ± 0.4 Mg ha −1 year −1 [4]. Litter decomposition of E. pellita in this environment was rapid, with 91.0% of leaves, 71.0% of twigs, and 71.2% of noncommercial stems (diameter < 5 cm) being completely decomposed within 18 months [18].…”
Section: Influence Of Fertilisation In Mid-rotation On Productivitymentioning
confidence: 99%
See 3 more Smart Citations